Satisfaction and Self-Confidence of Moroccan Nursing Students in Simulation-Based Learning and Their Associations with Simulation Design Characteristics and Educational Practices - Hicham Blaak; Abdelmajid Lkoul; Hayat Iziki; Abdelhadi El Haddaouy; Ahmed Kharabch; Rachid Razine; Lahcen Belyamani; Majdouline Obtel (Nursing Reports)
Background: Nursing students must be able to enter clinical practice as safe, accurate, competent, and compassionate professionals. Objectives: The aim of this study was to investigate the effectiveness of simulation training on the satisfaction and self-confidence of undergraduate nursing students. Methods: A cross-sectional and correlational study was conducted among 151 students enrolled in the third semester of nursing. Data were collected using a questionnaire comprising three instruments: SSSCL, SDS, and EPQ. Pearson’s correlation analysis was used to examine the relationship between satisfaction and self-confidence. Multiple linear regression was conducted to assess the influence of simulation design and various educational practices on students’ satisfaction and self-confidence. Results: The results revealed high mean scores for satisfaction (4.41 ± 0.40) and self-confidence (4.50 ± 0.36). A moderate, significant positive correlation was found between self-confidence and satisfaction (r = 0.579, p < 0.001). Furthermore, various learning methods (B = 0.112, p = 0.037, 95% CI [0.007; 0.217]) and objectives/information clarity (B = 0.175, p = 0.040, 95% CI [0.008; 0.342]) had a significant positive effect on satisfaction. Similarly, active learning (B = 0.146, p = 0.020, 95% CI [0.023; 0.268]) and feedback (B = 0.154, p = 0.035, 95% CI [0.011; 0.297]) had a significant positive effect on self-confidence. Conclusions: This study confirms that simulation-based training effectively boosts nursing students’ satisfaction and self-confidence, supporting its integration as a key component of nursing education to better prepare them for clinical challenges.